Interferon Beta Contributes to Astrocyte Activation in the Brain following Reovirus Infection - Clarke, Penny (J Virol, 2019)
Reovirus encephalitis in mice was used as a model system to investigate astrocyte activation (astrogliosis) following viral infection of the brain. Reovirus infection resulted in astrogliosis, as evidenced by increased expression of glial fibrillary acidic protein (GFAP), and the upregulation of genes that have been previously associated with astrocyte activation. Astrocyte activation occurred in regions of the brain that are targeted by reovirus but extended beyond areas of active infection. Astrogliosis also occurred following reovirus infection of ex vivo brain slice cultures (BSCs), demonstrating that factors intrinsic to the brain are sufficient to activate astrocytes and that this process can occur in the absence of any contribution from the peripheral immune response. In agreement with previous reports, reovirus antigen did not colocalize with GFAP in infected brains, suggesting that reovirus does not infect astrocytes. Reovirus-infected neurons produce interferon beta (IFN-β). IFN-β treatment of primary astrocytes resulted in both the upregulation of GFAP and cytokines that are associated with astrocyte activation. In addition, the ability of media from reovirus-infected BSCs to activate primary astrocytes was blocked by anti-IFN-β antibodies. These results suggest that IFN-β, likely released from reovirus-infected neurons, results in the activation of astrocytes during reovirus encephalitis. In areas where infection and injury were pronounced, an absence of GFAP staining was consistent with activation-induced cell death as a mechanism of inflammation control. In support of this, activated Bak and cleaved caspase 3 were detected in astrocytes within reovirus-infected brains, indicating that activated astrocytes undergo apoptosis. IMPORTANCE Viral encephalitis is a significant cause of worldwide morbidity and mortality, and specific treatments are extremely limited. Virus infection of the brain triggers neuroinflammation; however, the role of neuroinflammation in the pathogenesis of viral encephalitis is unclear. Initial neuroinflammatory responses likely contribute to viral clearance, but prolonged exposure to proinflammatory cytokines released during neuroinflammation may be deleterious and contribute to neuronal death and tissue injury. Activation of astrocytes is a hallmark of neuroinflammation. Here, we show that reovirus infection of the brain results in the activation of astrocytes via an IFN-β-mediated process and that these astrocytes later die by Bak-mediated apoptosis. A better understanding of neuroinflammatory responses during viral encephalitis may facilitate the development of new treatment strategies for these diseases.